VERNE HARRIS, Ghosts of Archive: Deconstructive Intersectionality and Praxis - Carlin, Isabel (Archivaria, 2022)
Ghosts of Archive: Deconstructive Intersectionality and Praxis. Verne Harris. London: Routledge, 2020. 166 pp. 9780429343827